Development of Plant-Puzzle Games (PPG) based on the Learning Styles of Junior High School Students to Increase Learning Motivation in Plant Classification Materials - Fitri Rizkiyah; Rizhal Hendi Ristanto; Mieke Miarsyah (Universitas Riau, 2022)
Plant classification material is one of the materials listed in the basic competence of the curriculum applied in Indonesia and is less attractive to students because the characteristics of plants are quite difficult to identify so that the classification is complicated. It is known that most middle-level students really like games which are integrated in learning activities. Therefore, this study aims to develop a media called Plant-Puzzle Games (PPG) which is expected to have a positive effect in the form of increasing the learning motivation of junior high school students in studying plant classification material. The research method used in this study is a research and development method with the ASSURE model as the research design. Based on the results of the media validation test by experts, an average value of 3.25 was obtained, which indicates that the media was included in the valid category. Based on the results of the effectiveness test with the calculation of N-Gain, the average value is 0.49. This shows that, after using PPG media, the learning motivation of students has increased which is in the sufficient category.